Electromagnetic shielding composite film with insulation-conduction alternating structure and preparation method of electromagnetic shielding composite film

By using an alternating structure of insulation-conductive structure in the composite film and using three-dimensional fractal silver dendrite/aramid nanofibers to construct conductive and insulating layers, the problem of difficult ultra-thin composite films in the prior art is solved, and the efficient electromagnetic shielding and thermal conductivity are achieved, which is suitable for the application of 5G technology.

CN119677080APending Publication Date: 2025-03-21SUN YAT SEN UNIV
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411800728.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

While maintaining ultra-thin thickness, it is difficult for the prior art to achieve excellent electromagnetic shielding and high thermal conductivity composite films at the same time. Especially in the context of the application of 5G technology, the demand for such materials has become more urgent.

Method used

Using the design of an insulation-conductive alternating structure, through alternating vacuum assisted suction filtration technology, three-dimensional fractal silver dendrite/aramid nanofibers (AgFDs/ANFs) are used as the conductive layer and insulating layer to build a hierarchical structure of the composite film to improve the perfection of the conductive network and thermal pathways.

Benefits of technology

It achieves high-efficiency electromagnetic shielding performance (60~120dB) and high thermal conductivity (30~80W m-1K-1) at ultra-thin thickness (≤20μm), which is significantly better than the uniform structure composite film, and is particularly suitable for electromagnetic shielding and thermal management of flexible electronic components.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses an electromagnetic shielding composite film with an insulation-conduction alternating structure and a preparation method of the electromagnetic shielding composite film. The electromagnetic shielding composite film is formed by alternately overlapping insulating layers and conducting layers, the number of the layers is an odd number larger than or equal to 3 and smaller than or equal to 7, and the insulating layers are arranged on the two sides of the conducting layers. The conductive layer is made of three-dimensional fractal silver dendritic crystal / aramid nanofiber; and the insulating layer is made of aramid nanofibers. The preparation method comprises the following steps: sequentially carrying out suction filtration on an ANFs dispersion liquid and an AgFDs / ANFs mixed dispersion liquid according to an insulation-conductive sequence by adopting an alternate vacuum-assisted suction filtration technology, and carrying out deionized water washing, drying and hot pressing on a wet film to prepare the composite film. The mass fraction of the prepared composite film AgFDs is 70-90%, the thickness is smaller than or equal to 20 microns, the electromagnetic shielding effectiveness is adjustable within 60-120 dB, the electromagnetic shielding effectiveness per unit thickness reaches 4000-8000 dB mm <-1 >, the heat conductivity is 30-80 W m <-1 > K <-1 >, and the composite film is suitable for electromagnetic shielding and heat management of flexible electronic devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of electromagnetic shielding composite film material processing, and specifically relates to an ultra-thin, high-efficiency and high-thermal-conductive electromagnetic shielding composite film with an insulating-conductive alternating structure and a preparation method thereof. Background Art

[0002] The development of ultra-thin, efficient and highly thermally conductive electromagnetic shielding composite films is an important method to solve the problems of electromagnetic interference, overheating and increased volume (thickness) caused by the development of electronic components and equipment towards high frequency, high speed, high heat flux density and thinness. Vacuum-assisted filtration technology has become a commonly used film-making method due to its simple process and the convenience of fine control of composite film parameters. For example, patent CN113788965A mixes carbon nanotubes and bacterial cellulose dispersions, and uses vacuum-assisted filtration technology to prepare bacterial cellulose modified buckypaper, whose thermal conductivity exceeds 7.393 W·m -1 ·K -1 , and when the thickness is 35μm, the electromagnetic shielding effectiveness reaches 24.01dB. Patent CN117384428A publicly reports that a mixed dispersion containing thiolated oxidized nanocellulose, silver nanoparticles and reduced graphene oxide is vacuum filtered to form a membrane. After drying and hot pressing, the composite membrane exhibits excellent electromagnetic shielding (67.58~98.05dB) and good thermal conductivity (16.19~18.82W·m -1 ·K -1 ) performance. On the other hand, based on the basic theory of electrical and thermal conductivity of polymer composite materials, people have proposed a multilayer structure design strategy to build an efficient conductive network and thermal conductivity path to further improve the electromagnetic shielding and thermal conductivity of the composite film. For example, patent CN114456443A publicly reported a "sandwich" structure of flexible cellulose / boron nitride / MXene composite film prepared by alternating vacuum-assisted filtration technology, with a thermal conductivity of 33.0 W·m -1 ·K -1 , the electromagnetic shielding effectiveness reaches 44.0dB. Patent CN115348815A discloses a self-supporting Co-MWCNTs@Fe3O4@MXene composite film prepared based on alternating vacuum assisted filtration technology. When the thickness is 38μm, its electromagnetic shielding effectiveness is as high as 57.8dB, and the thermal conductivity reaches 8.496W·m -1 ·K -1 However, it is still very difficult to obtain a composite film with both excellent electromagnetic shielding and thermal conductivity (≥60dB and ≥30W·m -1 ·K -1 ). Therefore, it is particularly important to develop a new type of ultra-thin, efficient and highly thermally conductive electromagnetic shielding composite film for 5G technology. Summary of the invention

[0003] In view of the deficiencies in the prior art, the object of the present invention is to provide an ultra-thin, efficient and highly thermally conductive electromagnetic shielding composite film with an insulating-conductive alternating structure and a preparation method thereof.

[0004] In order to achieve the above object, the present invention adopts the following technical solutions:

[0005] An electromagnetic shielding composite film with an insulating-conductive alternating structure, wherein the electromagnetic shielding composite film is formed by alternatingly overlapping insulating layers and conductive layers, the number of layers is an odd number greater than or equal to 3 and less than or equal to 7, and both sides of the conductive layer are insulating layers;

[0006] The conductive layer is three-dimensional fractal silver dendrite / aramid nanofiber (AgFDs / ANFs); the insulating layer is aramid nanofiber (ANFs).

[0007] Preferably, in the above-mentioned insulating-conductive alternating structure electromagnetic shielding composite film, the three-dimensional fractal silver dendrites refer to silver powders whose primary fractal structure is three-dimensionally radiating and has a size of 2 to 6 μm, and whose secondary and tertiary fractal structures have micro-nanoscale characteristics.

[0008] Preferably, in the above-mentioned insulating-conductive alternating structure electromagnetic shielding composite film, the aramid nanofiber refers to aramid fibers that are stirred and peeled in an alkaline dispersion to form deprotonated aramid nanofibers of nanometer size, and then an equal volume of deionized water is added under high-speed stirring conditions to obtain protonated aramid nanofibers with a diameter of 15 to 65 nm and a length of 10 μm.

[0009] A method for preparing an electromagnetic shielding composite film with an insulating-conductive alternating structure comprises the following steps: using an alternating vacuum-assisted filtration technique, filtering an aramid nanofiber dispersion and a three-dimensional fractal silver dendrite / aramid nanofiber mixed dispersion in the order of insulating-conductive, and preparing the wet film after washing with deionized water, drying and hot pressing.

[0010] Preferably, in the method for preparing the above-mentioned electromagnetic shielding composite film with an insulating-conductive alternating structure, the following steps are included:

[0011] (1) With the assistance of polyvinyl pyrrolidone, AgFDs are dispersed in dimethyl sulfoxide to prepare an AgFDs dispersion;

[0012] (2) Aramid fiber, dimethyl sulfoxide, potassium hydroxide and deionized water are stirred and mixed to prepare a deprotonated ANFs solution, referred to as ANFs solution, and then an equal volume of deionized water is slowly added to the solution under high-speed stirring conditions to obtain a protonated ANFs dispersion after removing bubbles, referred to as ANFs dispersion;

[0013] (3) The AgFDs dispersion obtained in step (1) and the ANFs dispersion obtained in step (2) are uniformly mixed to obtain an AgFDs / ANFs mixed dispersion, and the mixed dispersion is divided into N equal parts according to the number of conductive layers, 1≤N≤3, and then N+1 parts of the ANFs dispersion of the same mass are weighed, and the ANFs dispersion and the AgFDs / ANFs dispersion are filtered in the order of insulation-conductivity using a sand core filtration device with an inner diameter of 40 mm; after the filtration is completed, the wet membrane is washed with deionized water for multiple times, clamped by two PTFE plates, and placed in a blast drying oven for drying, and then the dry membrane is hot-pressed to obtain an electromagnetic shielding composite membrane with an insulating-conductive alternating structure.

[0014] Preferably, in the method for preparing the above-mentioned insulating-conductive alternating structure electromagnetic shielding composite film, the mass concentration of the AgFDs dispersion in step (1) is 0.5-2.0%, and the amount of polyvinyl pyrrolidone used is 0.5-1.5% of the mass of AgFDs.

[0015] Preferably, in the method for preparing the above-mentioned insulating-conductive alternating structure electromagnetic shielding composite film, the mass ratio of the aramid fiber, dimethyl sulfoxide and deionized water in step (2) is (0.5-1.5):(550-X):X, 10≤X≤20, X is a multiple of 5; the amount of KOH used is 1.0-2.0 times the mass of the aramid fiber. For example, it can be 0.5:540:10, 0.8:540:10, 1.0:535:15, 1.2:530:20 and 1.5:530:20, and the corresponding contents of the deprotonated ANFs solution are 1.0, 1.6, 2.0, 2.4 and 3.0 mg·mL -1 The amount of KOH used is 1.0 to 2.0 times the mass of the aramid fiber, for example, 1.0, 1.2, 1.4, 1.6, 1.8 and 2.0 times. During the preparation of the deprotonated ANFs solution, the stirring speed is set to 600 to 1000 r·min -1 , stirring time 6 to 10 hours. In the protonation stage, the speed of the high-speed stirring is set to 8000 to 12000 r·min -1 The stirring time is 30 to 90 minutes (including the time of adding deionized water). The amount of deionized water added is the same as the volume of the deprotonated ANFs solution, and the addition is completed within 15 minutes. After the protonation reaction, the concentration of ANFs is reduced to half of the original value.

[0016] Preferably, in the preparation method of the above-mentioned insulating-conductive alternating structure electromagnetic shielding composite film, the AgFDs / ANFs mixed dispersion in step (3) is used for filtering to construct the conductive layer of the composite film, wherein the absolute dry mass fraction of AgFDs is 95-98%, and the mixed dispersion is divided into N equal parts (where 1≤N≤3) according to the arrangement of the number of conductive layers. The ANFs dispersion is used to construct the insulating layer of the composite film, and N+1 parts of the same mass of ANFs dispersion are additionally weighed according to the arrangement of the number of conductive layers; the number of deionized water washing in step (3) is 3-5 times; the drying temperature in step (3) is set to 70-90°C, and the drying time is 12-24h; the hot pressing temperature is set to 100-130°C, the pressure is 25-30MPa, and the time is 0.5-2.0h; the mass fraction of AgFDs in the insulating-conductive alternating structure electromagnetic shielding composite film in step (3) is 70-90%, and the total thickness is ≤20μm.

[0017] The electromagnetic shielding composite film with the insulating-conductive alternating structure is used in electromagnetic shielding and thermal management of flexible electronic components.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] (1) The insulating-conductive alternating structure electromagnetic shielding composite film of the present invention uses three-dimensional fractal silver dendrites (AgFDs) with primary fractal structure presenting three-dimensional radiation and secondary and tertiary fractal structures having micro-nanoscale characteristics as conductive and thermal conductive fillers. AgFDs not only have the same high conductivity, high thermal conductivity and high stability as ordinary silver powder, but also the unique three-dimensional radial primary fractal structure is easy to form a three-dimensional filler network, which helps to improve the electromagnetic shielding and thermal conductivity of the composite film.

[0020] (2) Starting from the basic principles of electrical conductivity, electromagnetic shielding and thermal conductivity, the present invention proposes a strategy of constructing an insulating-conductive alternating structure instead of a uniform structure to prepare a high thermal conductivity and high efficiency electromagnetic shielding composite film. After the insulating-conductive alternating structure is designed, the content of AgFDs in the conductive layer of the composite film is increased, which effectively reduces the contact resistance and contact thermal resistance between the AgFDs, and the conductive network and thermal conduction path are more perfect. As a result, the electrical conductivity, electromagnetic shielding and thermal conductivity of the composite film are greatly improved. At the same time, when the number of conductive layers is ≥2, the loss path of electromagnetic waves inside the composite film increases, further improving the electromagnetic shielding performance of the composite film. The electromagnetic shielding effectiveness of the insulating-conductive alternating structure electromagnetic shielding composite film obtained by the present invention is adjustable within 60 to 120 dB under ultra-thin thickness (≤20 μm), and the electromagnetic shielding effectiveness per unit thickness reaches 4000 to 8000 dB·mm -1 , thermal conductivity is between 30 and 80 W m -1 K -1The electromagnetic shielding and thermal conductivity properties are significantly better than those of the uniform structure composite film, which is particularly suitable for electromagnetic shielding and thermal management of flexible electronic components. DETAILED DESCRIPTION

[0021] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0022] The sources of the components in the following examples are as follows: three-dimensional fractal silver dendrites (AgFDs), homemade in the laboratory; polyvinyl pyrrolidone (PVP, 10000 g·mol -1 ), potassium hydroxide (KOH, AR) and dimethyl sulfoxide (DMSO, AR) were purchased from Shanghai Aladdin Reagent Co., Ltd.; aramid fiber (brand: K49) was purchased from DuPont.

[0023] Embodiment 1:

[0024] This embodiment provides an ultra-thin, highly efficient and highly thermally conductive electromagnetic shielding composite film having an insulating-conductive alternating structure, and a preparation method thereof comprises the following steps:

[0025] (1) With the assistance of PVP (0.8% by mass of AgFDs), AgFDs were dispersed in DMSO to prepare a dispersion with an AgFDs content of 2.0% by mass.

[0026] (2) Aramid fiber, DMSO, deionized water and KOH were mixed in a mass ratio of 1.2:530:20:2.0 and stirred at a speed of 800 r min under magnetic stirring. -1 Stir in the dark for 8 h to prepare a solution with a content of 2.4 mg mL -1 The deprotonated ANFs solution (ANFs solution) was stirred at a rate of 8000 r min -1 An equal volume of deionized water was slowly added to the solution within 15 min, and the total stirring time was 60 min. Finally, after removing the bubbles, the ANF content was 1.2 mg mL -1 Protonated ANFs dispersion (abbreviated as: ANFs dispersion).

[0027] (3) 2.74g of AgFDs and 1.00g of ANFs dispersion were mixed evenly to obtain a mixed dispersion with an absolute dry mass fraction of AgFDs of 98%, and the number of conductive layers was set to 1. Then, 2 portions of 3.84g of ANFs dispersion were weighed, and the ANFs dispersion and the AgFDs / ANFs dispersion were filtered in the order of insulation-conductivity using a sand core filtration device with an inner diameter of 40mm. After the filtration, the wet film was washed with water 5 times, sandwiched between two PTFE plates, and placed in a blast drying oven for drying at 80°C for 12h. Finally, the dry film was placed in a hot press and hot pressed at 120°C and 30MPa for 1.0h to obtain an electromagnetic shielding composite film with 1 conductive layer and an insulation-conductivity alternating structure with an AgFDs mass content of 85%.

[0028] After testing, the total thickness of the composite film is 16μm, the electromagnetic shielding effectiveness in the X-band reaches 84.0dB, and the electromagnetic shielding effectiveness per unit thickness reaches 5250.0dB·mm -1 , thermal conductivity is 35.7 W·m -1 ·K -1 .

[0029] Embodiment 2:

[0030] This embodiment provides an ultra-thin, high-efficiency and high-thermal-conductivity insulating-conductive alternating structure electromagnetic shielding composite film, the preparation method of which includes the following steps:

[0031] (1) With the assistance of PVP (0.6% by mass of AgFDs), AgFDs were dispersed in DMSO to prepare a dispersion with an AgFDs mass content of 1.0%.

[0032] (2) Aramid fiber, DMSO, deionized water and KOH were mixed in a mass ratio of 1.0:535:15:1.5 and stirred at a speed of 800 r min under magnetic stirring. -1 Stir in the dark for 8 h to prepare a solution with a content of 2.0 mg mL -1 The ANFs solution was stirred at a rate of 10000 r min -1 An equal volume of deionized water was slowly added to the solution within 15 min, and the total stirring time was 45 min. Finally, after removing the bubbles, the ANF content was 1.0 mg mL -1 ANFs dispersion.

[0033] (3) 5.49 g of AgFDs and 1.20 g of ANFs dispersion were mixed evenly to obtain AgFDs / ANFs mixed dispersion. The number of conductive layers was set to 2, and the mixed dispersion was divided into 2 equal parts, i.e., 3.35 g each. Then, 3 parts of 3.07 g of ANFs dispersion were weighed, and ANFs dispersion and AgFDs / ANFs dispersion were filtered in the order of insulation-conductivity using a sand core filtration device with an inner diameter of 40 mm. After the filtration was completed, the wet film was washed with water three times, clamped by two PTFE plates, and placed in a blast drying oven for drying at 70°C for 24 hours. Finally, the dry film was placed in a hot press and hot pressed at 110°C and 28 MPa for 1.5 hours to obtain an electromagnetic shielding composite film with two conductive layers and an insulating-conductive alternating structure with an AgFDs content of 85%.

[0034] After testing, the total thickness of the composite film is 16μm, the electromagnetic shielding effectiveness in the X-band reaches 95.3dB, and the electromagnetic shielding effectiveness per unit thickness reaches 5956.3dB·mm -1 , thermal conductivity is 45.2W·m -1 ·K -1 .

[0035] Embodiment 3:

[0036] This embodiment provides an ultra-thin, high-efficiency and high-thermal-conductivity insulating-conductive alternating structure electromagnetic shielding composite film, the preparation method of which includes the following steps:

[0037] (1) With the assistance of PVP (1.0% by mass of AgFDs), AgFDs were dispersed in DMSO to prepare a dispersion with an AgFDs content of 0.5%.

[0038] (2) Aramid fiber, DMSO, deionized water, and KOH were mixed in a mass ratio of 0.8:540:10:1.0 and stirred at a speed of 600 r min under magnetic stirring. -1 Stir in dark for 8 h to prepare a solution with a content of 1.6 mg mL -1 The ANFs solution was stirred at a rate of 10000 r min -1 An equal volume of deionized water was slowly added to the solution within 15 min, and the total stirring time was 60 min. Finally, after removing the bubbles, the ANF content was 0.8 mg mL -1 ANFs dispersion.

[0039] (3) 10.98g of AgFDs and 1.51g of ANFs dispersion were mixed evenly to obtain AgFDs / ANFs mixed dispersion. The number of conductive layers was set to 3, and the mixed dispersion was divided into 3 equal parts, i.e., each part was 4.16g. Then, 4 parts of 2.88g of ANFs dispersion were weighed, and the ANFs dispersion and AgFDs / ANFs dispersion were filtered in the order of insulation-conductivity using a sand core filtration device with an inner diameter of 40mm. After the filtration was completed, the wet film was washed with water 5 times, clamped by 2 PTFE plates, and placed in a blast drying oven for drying at 80°C for 15h. Finally, the dry film was placed in a hot press and hot pressed at 120°C and 30MPa for 1.5h to obtain an electromagnetic shielding composite film with 3 conductive layers and an insulating-conductive alternating structure with an AgFDs mass content of 85%.

[0040] After testing, the total thickness of the composite film is 15μm, the electromagnetic shielding effectiveness in the X-band reaches 103.9dB, and the electromagnetic shielding effectiveness per unit thickness reaches 6926.7dB·mm -1 , thermal conductivity is 39.3W·m -1 ·K -1 .

[0041] Comparative Example 1

[0042] This embodiment provides a uniform structure AgFDs / ANFs electromagnetic shielding composite film as a comparative example of an insulating-conductive alternating structure electromagnetic shielding composite film, and its preparation method includes the following steps:

[0043] (1) With the assistance of PVP (0.6% by mass of AgFDs), AgFDs were dispersed in DMSO to prepare a dispersion with an AgFDs content of 1.0% by mass.

[0044] (2) 5.49 g of AgFDs dispersion and 10.41 g of ANFs dispersion (1.0 mg mL -1 ) were mixed evenly to obtain a AgF / ANFs mixed dispersion, and then the dispersion was filtered. The wet membrane was washed three times with deionized water, clamped with two PTFE plates, and placed in an oven to dry at 70°C for 24h. Finally, the dry membrane was hot-pressed at 110°C and 28.0MPa for 1.5h to obtain a uniform structure AgFDs / ANFs electromagnetic shielding composite membrane with an AgFDs mass fraction of 85%.

[0045] After testing, the total thickness of the composite film is 17μm, the electromagnetic shielding effectiveness in the X-band reaches 53.5dB, and the electromagnetic shielding effectiveness per unit thickness is 3147.1dB·mm -1 , thermal conductivity is 26.4W·m -1 ·K -1 .

Claims

1. An electromagnetic shielding composite film with an insulating-conductive alternating structure, characterized in that: The electromagnetic shielding composite film is formed by alternately overlapping insulating layers and conductive layers, the number of layers is an odd number greater than or equal to 3 and less than or equal to 7, and both sides of the conductive layer are insulating layers; The conductive layer is three-dimensional fractal silver dendrite / aramid nanofiber; and the insulating layer is aramid nanofiber.

2. The electromagnetic shielding composite film with an insulating-conductive alternating structure according to claim 1, characterized in that: The three-dimensional fractal silver dendrite refers to a silver powder whose primary fractal structure is three-dimensionally radiating and has a size of 2 to 6 μm, and whose secondary and tertiary fractal structures have micro-nanoscale characteristics.

3. The electromagnetic shielding composite film with an insulating-conductive alternating structure according to claim 1, characterized in that: The aramid nanofibers are deprotonated aramid nanofibers of nanometer size formed by stirring and peeling aramid fibers in an alkaline dispersion, and then protonated aramid nanofibers with a diameter of 15 to 65 nm and a length of 10 μm are obtained by adding an equal volume of deionized water under high-speed stirring conditions.

4. A method for preparing the electromagnetic shielding composite film with an insulating-conductive alternating structure as claimed in claim 1, characterized in that The method comprises the following steps: adopting alternating vacuum-assisted filtration technology, filtering aramid nanofiber dispersion and three-dimensional fractal silver dendrite / aramid nanofiber mixed dispersion in the order of insulation-conductivity, and preparing the wet membrane after washing with deionized water, drying and hot pressing.

5. The method for preparing the electromagnetic shielding composite film with an insulating-conductive alternating structure according to claim 4, characterized in that The following steps are involved: (1) With the assistance of polyvinyl pyrrolidone, AgFDs are dispersed in dimethyl sulfoxide to prepare an AgFDs dispersion; (2) Aramid fiber, dimethyl sulfoxide, potassium hydroxide and deionized water are stirred and mixed to prepare a deprotonated ANFs solution, referred to as ANFs solution, and then an equal volume of deionized water is slowly added to the solution under high-speed stirring conditions to obtain a protonated ANFs dispersion after removing bubbles, referred to as ANFs dispersion; (3) The AgFDs dispersion obtained in step (1) and the ANFs dispersion obtained in step (2) are uniformly mixed to obtain an AgFDs / ANFs mixed dispersion, and the mixed dispersion is divided into N equal parts according to the number of conductive layers, 1≤N≤3, and then N+1 parts of the ANFs dispersion of the same mass are weighed, and the ANFs dispersion and the AgFDs / ANFs dispersion are filtered in the order of insulation-conductivity using a sand core filtration device with an inner diameter of 40 mm; after the filtration is completed, the wet membrane is washed with deionized water for multiple times, clamped by two PTFE plates, and placed in a blast drying oven for drying, and then the dry membrane is hot-pressed to obtain an electromagnetic shielding composite membrane with an insulating-conductive alternating structure.

6. The method for preparing the electromagnetic shielding composite film with an insulating-conductive alternating structure according to claim 5, characterized in that The mass concentration of the AgFDs dispersion in step (1) is 0.5-2.0%, and the amount of polyvinyl pyrrolidone used is 0.5-1.5% of the mass of AgFDs.

7. The method for preparing the electromagnetic shielding composite film with an insulating-conductive alternating structure according to claim 5, characterized in that In step (2), the mass ratio of the aramid fiber, dimethyl sulfoxide and deionized water is (0.5-1.5):(550-X):X, 10≤X≤20, X is a multiple of 5, and the amount of KOH used is 1.0-2.0 times the mass of the aramid fiber.

8. The method for preparing the electromagnetic shielding composite film with an insulating-conductive alternating structure according to claim 5, characterized in that The number of deionized water washing in step (3) is 3 to 5 times; the drying temperature is set to 70 to 90° C., and the drying time is 12 to 24 hours; the hot pressing temperature is set to 100 to 130° C., the pressure is 25 to 30 MPa, and the time is 0.5 to 2.0 hours.

9. Use of the electromagnetic shielding composite film with an insulating-conductive alternating structure according to any one of claims 1 to 3 in electromagnetic shielding and thermal management of flexible electronic components.

Citation Information

Patent Citations

  • Composite film with electromagnetic shielding and heat-conducting properties and preparation method thereof

    CN115348815A

  • Flexible composite film with electromagnetic shielding performance and thermal conductivity as well as preparation method and application of flexible composite film

    CN117384428A

  • Conductive composite material and preparation method thereof, and preparation method for conductive line

    CN105006270A

  • Flexible electromagnetic shielding composite material and preparation method thereof

    CN111138836A

  • Nanocellulose / MXene / silver nanowire sandwich structure composite film and preparation method thereof

    CN113072725A